Nation Branding of Kepulauan Riau Through Subregional Cooperation in The Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) - Rizqi Apriani Putri; Ella Afnira (Journal of Maritime Policy Science, 2024)
Nation branding has become a key element in modern communication strategies, particularly in the context of globalization. Countries strive to establish a positive international image, reflecting their unique identity and values. Nation branding is a marketing and communication strategy aimed at enhancing a country’s image, both domestically and globally. Kepulauan Riau participation in the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) cooperation, and its hosting of the IMT-GT event in 2023, represents an effort to strengthen its image internationally. The IMT-GT is a subregional economic collaboration involving Indonesia (Sumatra), Malaysia, and Thailand, with the Kepulauan Riau being an active participant. This research utilizes a descriptive-analytical approach, supported by secondary data, to examine the impact of this initiative. One of the notable implementations of this cooperation is the IMT-GT Expo "Gebyar Melayu Pesisir," which showcases Kepulauan Riau local culture and products. This event aims to foster economic growth among the three countries, particularly in the Kepulauan Riau as the host region. The outcomes of the IMT-GT initiatives include agreements that enhance connectivity among member countries, fostering an integrated, innovative, inclusive, green, and sustainable growth strategy, with a vision extending to 2036. This research highlights the potential for the Kepulauan Riau to leverage nation branding through subregional cooperation, enhancing economic growth and international recognition.